2021
DOI: 10.2147/cia.s321921
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of High-Risk Factors Associated with the Progression of Subaneurysmal Aorta to Abdominal Aortic Aneurysm in Rural Area in China

Abstract: Objective: To determine the risk factors associated with the progress of subaneurysmal aorta (SAA) to abdominal aortic aneurysm (AAA) and provide a reference for the prevention of AAA in rural areas. Methods: A total of 747 SAA patients screened by the Health Management Center of the Second Hospital of Lanzhou University from January 2015 to January 2016 were recruited. The ratio of SAA progressing to AAA was observed through 5 years of follow-up. Logistic stepwise regression analysis was performed to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The reported risk factors for AA included male sex [ 27 , 28 ], white race [ 28 ], smoking [ 27 , 28 ], hypertension [ 27 ], high low-density lipoprotein [ 28 ], and hypercholesteremia [ 28 30 ]. For the Chinese population, it was reported that age, smoking habits, degree of hypertension, and poor control of hypertension were high-risk factors for the formation and progression of AAA [ 31 ]. In our present study, the most predominant attributable risk factors for AA burden were high systolic blood pressure and smoking; in addition, the AA-induced death rate attributed to these two risk factors was higher in males.…”
Section: Discussionmentioning
confidence: 99%
“…The reported risk factors for AA included male sex [ 27 , 28 ], white race [ 28 ], smoking [ 27 , 28 ], hypertension [ 27 ], high low-density lipoprotein [ 28 ], and hypercholesteremia [ 28 30 ]. For the Chinese population, it was reported that age, smoking habits, degree of hypertension, and poor control of hypertension were high-risk factors for the formation and progression of AAA [ 31 ]. In our present study, the most predominant attributable risk factors for AA burden were high systolic blood pressure and smoking; in addition, the AA-induced death rate attributed to these two risk factors was higher in males.…”
Section: Discussionmentioning
confidence: 99%